2006
DOI: 10.1681/asn.2005101038
|View full text |Cite
|
Sign up to set email alerts
|

Regional Arterial Stiffness in Patients with Type 2 Diabetes and Chronic Kidney Disease

Abstract: Increased arterial stiffness is an independent predictor of death from cardiovascular disease, and aortic stiffness is more predictive than stiffness of other arterial regions. Because little is known about the effect of chronic kidney disease (CKD) on regional arterial stiffness, pulse wave velocity (PWV) of four different arterial segments was measured in patients who had type 2 diabetes with and without various stages of CKD. A total of 434 patients had type 2 diabetes, and there were 192 healthy control su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(64 citation statements)
references
References 38 publications
4
57
1
2
Order By: Relevance
“…Previous studies 20,22) identified age, diabetes mellitus, and CKD as the factors preferentially associated with increased PWV of the aorta over other arterial segments. Thus, we examined whether baPWV shared such risk factors with aortic PWV in our subjects.…”
Section: Individual Factors Correlating With Pwvmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies 20,22) identified age, diabetes mellitus, and CKD as the factors preferentially associated with increased PWV of the aorta over other arterial segments. Thus, we examined whether baPWV shared such risk factors with aortic PWV in our subjects.…”
Section: Individual Factors Correlating With Pwvmentioning
confidence: 99%
“…PWV and blood pressure measurements were performed in the supine position after 5 minutes of bed rest using an automatic waveform analyzer (model BP-203RPE; Colin, Komaki City, Japan) as previously described 20,22,25) . The ankle-brachial pressure index (ABI) was defined as the ratio of systolic blood pressure (SBP) of the tibial artery to that of the brachial artery.…”
Section: Pwv and Blood Pressure Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the role of dyslipidemia in advanced atherosclerosis in patients with CKD, both carotid IMT 52,56) and aortic PWV 53,54,57) are reported to be positively associated with non-high-density lipoprotein cholesterol (non-HDL-C), independent of other risk factors in subjects with various degrees of CKD. Among non-HDL lipoproteins, IDL showed the closest association with aortic PWV in hemodialysis patients 53) .…”
Section: Lipid-lowering Treatment and Risk For Cvd In Early Stages Ofmentioning
confidence: 99%
“…В этой связи, всё больше исследователей начинают обращать своё внимание на вопросы ранней диагно-стики и профилактики сосудистых осложнений при ХБП. В частности, в ряде работ показано, что при выраженной почечной дисфункции усиливается артериальная жесткость [17], повышается скорость пульсовой волны [11] и снижается эластичность магистральных сосудов [7]. Однако половые харак-теристики поражения каротидных артерий и их взаимосвязь с дисфункцией почек при ГН изучены недостаточно.…”
Section: Introductionunclassified